Principals’ Organizational Management and Teachers’ Efficiency among Public Basic Schools in Ilorin West Local Government Area, Kwara State - ADEDOKUN, Femi Johnson; LAWAL, Abdulmumin Abubakar (Ilorin Journal of Education, 2023)
This study focused on the organizational management of the principals and the efficacy of the teachers in the public elementary schools of Ilorin West Local Government Area of Kwara State. The researchers used a survey, correlational study approach. As at August 20, 2022, the population for the research included all 29 principals and 789 teachers from the 29 public basic schools in Ilorin West Local Government Area, Kwara state. An overall of 303 respondents were chosen at random for this article, consisting of 274 instructors and 29 principals, respectively. For the study, questionnaires labeled "Principals’ Organizational Management Questionnaire (POMQ) and Teachers’ Efficiency Questionnaire (TEQ)" were employed. The instrument was validated and evaluated for validity and reliability by specialists. POMQ and TEQ achieved reliability ratings of 0.61 and 0.64, respectively. While inferential statistics of Pearson product-moment correlation statistics were employed to test the hypothesis at a 0.05 degree of significance, descriptive statistics of mean and standard deviation were utilized to answer research questions. The study’s conclusions showed that: the organizational management of principals at public basic schools in Ilorin West Local Government Area, Kwara State, was average; and there was a strong link between principals’ organizational management and teachers’ efficacy in those schools. Based on the research’s findings and conclusions, to raise the caliber of instruction, it was recommended, along with many other factors, that principals undertake effective and efficient ways supervision.